1986
DOI: 10.1055/s-2008-1025781
|View full text |Cite
|
Sign up to set email alerts
|

Improved Insulin Sensitivity in Carbohydrate and Lipid Metabolism After Physical Training

Abstract: To estimate physical training effects quantitatively, the relationship between tissue sensitivity to exogenous insulin (glucose metabolism determined by euglycemic insulin-clamp technique) and maximal oxygen uptake (VO2 max) was defined in 9 well-trained athletes and 14 untrained subjects with normal glucose tolerance. Tissue sensitivity to exogenous insulin in the athletes was significantly higher than in the controls (P less than 0.001). Seven untrained subjects continued the physical exercise program. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Since we could ®nd no other training studies that involved normal children, we can only compare our results to those involving adults. Our results agree with the ®ndings from some of those studies (Sato et al 1986;Segal et al 1991;Soman et al 1979). However, our results are in contrast to previous cross-sectional studies (LeBlanc et al 1979;Pratley et al 1995) and longitudinal studies involving adults (Bursztyn et al 1993;Hurley et al 1991) that have indicated that training decreases glucose levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since we could ®nd no other training studies that involved normal children, we can only compare our results to those involving adults. Our results agree with the ®ndings from some of those studies (Sato et al 1986;Segal et al 1991;Soman et al 1979). However, our results are in contrast to previous cross-sectional studies (LeBlanc et al 1979;Pratley et al 1995) and longitudinal studies involving adults (Bursztyn et al 1993;Hurley et al 1991) that have indicated that training decreases glucose levels.…”
Section: Discussionsupporting
confidence: 90%
“…This change in insulin level has been demonstrated in both the adult-onset diabetic population (Zinamann et al 1982) and in normal adults (LeBlanc et al 1981;King et al 1987;Sato et al 1986). We now report a similar response in children.…”
Section: Discussionsupporting
confidence: 80%
“…Studies showing significant reductions in body fat with exercise training have typically used training durations of 9 ± 12 months [13,24], and thus our training duration may have been insufficient for appreciable changes in body composition. However, our finding that FFA levels were unchanged while fasting insulin levels decreased after RT may indicate that RT improved the ability of insulin to suppress FFA, which has been shown following one month of exercise [23].…”
Section: Discussionmentioning
confidence: 60%
“…Despite the lower insulin levels, glucose tolerance remains normal or improves in the trained state (1, 9, 16). Furthermore, we have reported that glucose disposal is increased in trained subjects using the euglycemic clamp procedure, which maintains plasma insulin and glucose concentrations at constant physiological levels (19, 22,23). Looking at this evidence, physical training appears to…”
Section: Introductionmentioning
confidence: 93%